MODEL IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PENDEKATAN TERINTEGRASI DALAM PERKULIAHAN PADA JURUSAN PAI – FITK UIN MAULANA MALIK IBRAHIM MALANG - Mujtahid, Mujtahid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The objective of this research is to meticulously investigate the model of character education implementation by the use of integrated approach during the course at Islamic Education in the Faculty of Tarbiyah and Teacher Training, Maulana Malik Ibrahim State Islamic University of Malang. It focuses on three points encompassing religious, self-personality and social characters that were developed in the learning and teaching process. By purposively selecting the analytical-critical-descriptive approach, the research data were qualitatively obtained by interviews, observations and documentations. The findings reveal three main aspects. The first is a model of religious character that is constructed by thoyyibah texts (basmallah and hamdalah), reciting al Quran, prayers, and dzikr as the manifestation of pious values and beliefs to Allah. The second point is self-personality model as the character construction that is instilled through the familiarization of discipline, sincerity and responsibility during the courses that involve learning process, instructional practice and learning evaluation. The third is the construction of social characters including tolerance, social respects and real democracy in learning system.